Eight new triterpenoids isolated from dysoxylum grande (meliaceae) by various chromatographic techniques. - Ismail, Intan Safinar; Low, K. W. (2012)

(untitled)
Due to the lack of scientific investigation on Dysoxylum grande, chemical investigation on this plant icthyotoxic leaves was done. Thorough fractionation using various chromatographic techniques including High Performance Liquid Chromatography (HPLC) has led to the isolation and characterization of eight new triterpenoids. The new compounds were named as grandol A(1), B(2), C(3), D(4), E(5), F(6) and G(7)H. Another compound having a different configuration at C24 was assign as the new 20S, 24R0epoxy-7b, 25-dihydroxy-34-secodammar-4(28)-en-3-oic acid (8). All compounds were elucidated based on various spectroscopic data. Their relative configuration was established by 2D NMR data of NOESY. All compounds were tested for anti-acetylcholinesterase using Thin Layer Chromatography (TLC)-bioautography with fast blue B salt. Only grandol A91) and B(2) showed positive results with clear discoloration until at the concentration of 12.5 ppm. However, the obtained IC50 for both grandol A and B when using Ellman's method, was not significant (>200ug/ml) compared to galanthamine (1.955 ug/ml) or huperzine A (0.082 ug/ml[1,2]